Diabetes and cardiovascular disease: let’s push forward with translational research - Paneni, Francesco (Cardiovasc Diagn Ther, 2015)
Albeit advances in therapy have reduced morbidity and mortality in patients with diabetes, cardiovascular (CV) risk is far to be eradicated. This is partially due to the fact that breakthrough therapies have yet to be approved to counteract the atherosclerotic burden in this setting. Therefore, it is very important to understand the molecular mechanisms underpinning diabetes-related CV complications. Growing evidence is supporting the concept that translational research is perhaps the best approach to unveil novel insights into disease etiology and its link with CV phenotypes. The recent employment of high throughput “omics” (i.e., metabolomics, transcriptomics, proteomics) is a clinically relevant approach which may provide insightful interpretations of diabetes-related biological signals. The possibility to analyse thousands or more molecules simultaneously has given “omics” the ability to generate enormous quantities of data which may somehow offer a precious “window on the disease”. In the present article, we critically discuss the importance of translational research in diabetes, including potential difficulties which may arise in the implementation and development of promising technologies from the laboratory to the marketplace.